The Effect of Genially Media-Assisted Gamification on Student Learning Motivation in IPAS Subjects in Grade V of SD Negeri 3 Palu - Moh Asyadi; Zulnuraini Zulnuraini; Khairunnisa Khairunnisa; Azizah Azizah; Andi Nur Isnayanti (FKIP - Universitas Riau, 2026)
Learning motivation is crucial in basic education, but monotonous activities often reduce student engagement. This study investigates the effect of gamification supported by Genially media on fifth-grade students' desire to learn. The quantitative methods used were a quasi-experimental design for non-equivalent control groups. The population consisted of fifth-grade students, with a sample of 57 students selected through purposive sampling, It consisted of an experimental group of 28 students in Class A and a control group of 29 students. Data was collected through a validated and reliable questionnaire. Analyzed using Normality, Homogeneity, and Independent Sample t-Test with Welch's correction. Based on these findings, the average posttest score for the experimental class was 87.21, which was much higher than the control class score of 78.03. The independent sample t-test showed a significance value of (2-tailed) < 0.001. It was concluded that Genially-assisted gamification had a significant effect on increasing student learning motivation by creating an interactive, challenging, and enjoyable learning atmosphere.